Stakeholders’ Perception Regarding Sustainable Universities - Nicolae Al. Pop; Steluța Todea; Cristina-Veronica Partenie; Cristina Ott (Amfiteatru Economic)
The aim of the study is to determine and confirm the main vectors that define the concept of sustainable university based on the example of a higher education institution that is representative for the Romanian economic higher education system. As objectives the authors defined the following: clarifying the concept of sustainable university based on the literature review; determining the main groups of stakeholders of the university and classifying them tridimensional; researching the perception regarding the vectors needed for the sustainable development of the university. The research stems from the three main stakeholders’ categories, in the authors’ opinion. A quantitative marketing research was undertaken on two main stakeholders’ categories: students, and representatives of the business environment that are part of the Alumni Association of the university. Using the factor analysis, the four vectors that define, in the authors opinion, the sustainable university were validated, which was confirmed. A qualitative research based on a focus group among academia and management counterbalanced the results of the study, confirming through results the stated hypotheses. The limitations of the current study stem from the involvement of only a part of the university’s stakeholders. Future research could investigate the perception of other stakeholders.